Design of an integrated library system with metadata schema creation and selection through entity relationship modeling of selected special libraries in Metro Manila - Santillan, Sara Gabriella L. (School of Library and Information Studies, University of the Philippines Diliman, 2010)
The field of information science continues to expand, and as such new fields of inquiry must be answered in conjunction with methods imbibed by the field through its interdisciplinary nature. The study of library automation has received some attention in the past, but never in conjunction with the recent developments in metadata standards or with the intent to design integrated library systems (ILSs). The research focused on special libraries in Metro Manila to see if their particular institutions had different data fields other than the AACR2R standard and/or had special vocabularies for their field of specialization, and what data was recorded for their processes. The data gathered served as a basis for creating the design of the ILS.